2020
DOI: 10.1101/2020.06.24.168450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A robust and self-sustained peripheral circadian oscillator reveals differences in temperature compensation properties with central brain clocks

Abstract: Circadian clocks temporally organize physiology and behavior of organisms exposed to the daily changes of light and temperature on our planet, thereby contributing to fitness and health. Circadian clocks and the biological rhythms they control are characterized by three properties. (1) The rhythms are self-sustained in constant conditions with a period of ~ 24 hr,(2), they can be synchronized to the environmental cycles of light and temperature, and (3), they are temperature compensated, meaning they run with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Next we analyzed the expression of a tim-luciferase (ptim-TIM-LUC) reporter gene that accurately reflects temporal TIM expression in peripheral clock cells (29,36). In a wild type background, ptim-TIM-LUC oscillations were indistinguishable at 18°C and 25°C, while oscillations were reduced in amplitude at 29°C (Figure S4A), similar to what we observed for BG-luc (Figure 4A).…”
Section: The Per I530a Mutation Affects Per and Tim Stability And Post-translational Modification At Higher Temperatures During Ddsupporting
confidence: 67%
See 3 more Smart Citations
“…Next we analyzed the expression of a tim-luciferase (ptim-TIM-LUC) reporter gene that accurately reflects temporal TIM expression in peripheral clock cells (29,36). In a wild type background, ptim-TIM-LUC oscillations were indistinguishable at 18°C and 25°C, while oscillations were reduced in amplitude at 29°C (Figure S4A), similar to what we observed for BG-luc (Figure 4A).…”
Section: The Per I530a Mutation Affects Per and Tim Stability And Post-translational Modification At Higher Temperatures During Ddsupporting
confidence: 67%
“…Although it can be argued that signals were recorded from specific neuronal subsets, these subsets within the context of the entire network, which could of course influence the oscillations within one group. Nevertheless, even in the background of a Pdf 01 mutation, which largely prevents network coupling due to the lack of the PDF neuropeptide (17), temperature compensated clock gene expression was observed in dorsal subsets of the clock neurons (29). However, the same study revealed that circadian clocks in isolated fly tissues (in halteres and antennae) are over compensated, pointing to differences between neuronal and non-neuronal circadian clocks (29).…”
Section: Temperature Compensation: Network Versus Cell Autonomous Propertymentioning
confidence: 95%
See 2 more Smart Citations
“…The experiments were repeated three times and the total average is shown in Figure 4. For the statistical analysis of the data, estimation statistics was used 47 . Data were analyzed using DABEST 48 , using the website available under https://www.estimationstats.com/#/.…”
Section: Long-day Behaviormentioning
confidence: 99%